FORMULASI STRATEGI PENINGKATAN PRODUKSI DOMBA CV MITRA TANI FARM, CIAMPEA, BOGOR - Amalia Sholehana; Rizal Syarief; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2012)
ABSTRACTThis research was conducted to formulate to increase the sheep production at CV Mitra Tani Farm (CV MT Farm), Ciampea, Bogor. The research was conducted using descriptive analysis by analyzing the problem experienced by CV. MitraTani Farm. Primary data and secondary data were gathered at this research. The research was also conducted using several analytical methods such as value chain mapping, internal factor evaluation (IFE) and external factor evaluation (EFE) matrix, SWOT and quantitative strategic planning matrix (QSPM). Based on the value chain analysis, the current production of sheep at CV MT farm is highly depending on the supply from its partners and internal farmers. According to the IFE and EFE results, the differences of each weighted values were respectively 2,120 and 0,686 so the position of the company in the SWOT matrix was situated at Quadrant I. Therefore the company needs to use a growth strategy. The QSPM sequenced the strategy priority as follow (1) increasing the number of lambs, (2) developing the management, (3) strengthening the capital and ownership, (4) improving the quality through technology. The result of the gross profit margin calculation, if the sheep‘s selling is increased up to 1000 sheep per month then the possible annual profit that can be earned by CV MT farm is 40,34% of the total production.Keywords: MT Farm, sheep production, strategies, SWOT, QSPM, gross profit marginABSTRAKPenelitian ini dilakukan untuk memformulasikan strategi peningkatan produksi domba di CV Mitra Tani Farm (CV MT Farm), Ciampea, Bogor. Pendekatan penelitian yang diterapkan adalah analisis deskriptif yang dilakukan dengan mempelajari permasalahan dari objek yang diteliti. Data yang dikumpulkan dalam penelitian ini adalah data primer dan data sekunder. Penelitian dilakukan menggunakan alat analisis berupa pemetaan rantai nilai, matriks IFE (Internal Factor Evaluation) dan EFE (External Factor Evaluation), SWOT, dan QSPM (Quantitative Strategic Planning Matrix). Hasil analisis rantai nilai diketahui bahwa produksi domba di CV MT farm saat ini sangat tergantung dari pasokan mitra dan petani internal. Hasil IFE dan EFE diperoleh selisih nilai tertimbang masing-masing sebesar 2,120 dan 0,686 maka diperoleh posisi perusahaan dalam matrik SWOT berada pada kuadran I. Oleh karena itu, perusahaan disarankan untuk menggunakan strategi pertumbuhan. Urutan prioritas strategi berdasarkan QSPM adalah (1) meningkatkan jumlah bakalan, (2) pengembangan manajemen, (3) memperkuat modal dan kepemilikan, (4) meningkatkan kualitas melalui teknologi. Hasil perhitungan gross profit margin diketahui keuntungan yang diperoleh CV MT farm setiap tahunnya jika meningkatkan penjualan domba mencapai 1000 ekor/bulan adalah sebesar 40,34% dari total produksi. Kata kunci: MT Farm, produksi domba, strategi, SWOT, QSPM, gross profit margin